(3MGTjI Ydi GdahGFO GdVjGFjI TQM GdcGajI ddLGejs - (3GdCSaQGjjfj, GdYUGe, EHQGgje Hf eMeO Hf YQH TGg, J(B945(3g`s
(3ChdgG (B:s
(3fGbU GdChd, hjHOC YfO bhdg(B: (3GdJHjjf GdCXgQ TQW JCKjQg heG PcQg HYjO Yf Gdage, bhdg(B: (3hgj UjZI GdJj cGf ChdgG de jbd hgj eG CTGQ Edjg HGdeKGdjf eY Cfg GdCNUQ dCf GdeKGdjf Ydi hRf eaGYd heaGYjd aNQL Yfg HXGgQ LYGaQ hLeGgQs
(3BNQgG (B:s
(3fGbU GdBNQ, hjfJgj YfO bhdg(B: (3aGdeaJhM eG bHdgG JbdH CdaG HfGA GdcJGHI aj GdCNQ Ydi Gdhba haj GdChd Ydi GdGHJOGA ceG JbQQ aj eMdg jhLH Cf dG jcJH GdNajaI GdJj de jaJM eG bHdgG hjcJH CdaG EPG GfaJM eG bHdgG acJGHJgG Ydi NdGa GdbjGSs
(3JhLO WjGQGJ aj YOI ehGVY ef GdfSNIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 1 / 66s
(3eYLe GdeDdajf(B: 1 / 67s
(3cTa GdXfhf(B: 2 / 1372s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdfMhs